Aeronautical engineers' data book - Matthews, Clifford (Butterworth-Heinemann, 2002)
This is an essential handy guide containing useful up to date information regularly needed by the student or practising engineer. Covering all aspects of aircraft, both fixed wing and rotary craft, this pocket book provides quick access to useful aeronautical engineering data and sources of information for further in-depth information. Quick reference to essential data Most up to date information available.
Keywords: Aeronautics -- Handbooks, manuals, etc.; elektronické knihy; electronic books